Development of a low cost two axis force sensor - Rahman, Md. Mozasser; Khairul Hassan, SK; Choudhury, Tasnuva Tabashhum (International Foundation for Modern Education and Scientific Research, IFOMESR, 2013)
This paper presents a low cost smart two axis force sensor with Analog-to-Digital (RS232 and SPI) interfaces, especially suitable for measuring low and moderate forces. A mechanical structure is made by rapid prototyping machine. Pair of resistive sensor is used for each axis. A computer controlled 12-bit A/D converter is employed to obtain a higher resolution. The nonlinear output of the sensor converts to linear output by piecewise linearization technique. A digital 60 Hz notch filter is implemented in the micro computer for rejecting the Ac supply noise. Third order digital FIR filter is used for removing noise from final output. Filtered data is converted into pulse width modulation where duty cycle is proportional to applied force. The filtered data is converted into Digital RS232 and SPI format for interfacing the digital world. Finally the performances of the sensor have been justified.